IDIOPATHIC FORM OF ATRIAL FIBRILLATION, INFLAMMATION AND CLINICAL RESULTS OF RADIOFREQUENCY ABLATION - R. E. Batalov; Yu. V. Rogovskaya; V. V. Ryabov; R. B. Tatarsky; S. I. Sazonova; M. S. Khlynin; S. V. Popov; R. S. Karpov (Российский кардиологический журнал, 2014)
Aim. To evaluate  the impact of inflammation on clinical results  of radiofrequency ablation (RFA) for atrial fibrillation (AF).Material and methods. Totally 274 patients studied,  admitted to the hospital with the  diagnosis  idiopathic  AF,  of those  just  67  (24,5%)  had  this  diagnosis  been confirmed  at  previous  stage   of  clinical  assessment.  All   patients   underwent intracardiac investigation and RFA AF, endomyocardial byopsy (EMB) with histologic and  immunohistochemical   studies   for  immunophenotype   cells  study  of  the endomyocardial infiltrate and revealing of cardiotropic viruses antigenes expression: to parvovirus B19, enterovirus,  virus human  herpes  1 and  2 types,  adenovirus, cytomegalovirus,  Epstein-Barr  virus. We studied  efficacy of catheter treatment, development of early and late recurrent  episodes of atrial tachiarrhythmias.Results. Histologic changes in right ventricle myocardium  were not found in 9 (13,4%) patients.  In 26 (38,8%) we found fibrous changes of myocardium: in 11 (42,3%)  — mostly perivascular  fibrosis,  in 8 (30,8%)  — small-nodular,  in 7 —(26,9%) — perimuscular.  Inflammatory changes (according to Dallas criteria) were marked in 32 (47,8%) patients,  of those in 9 (28,1%) lymphocyte infiltration found (less  than  14  lymphocytes  mm ).  In one  of these   patients  (3,1%)  there  was combination  of herpes  sumplex virus 2nd type and  Epstein-Barr.  In 23 patients (34,3%), myocarditis found, of those in 18 (78,3%) virus expression  found. In one (5,6%) patient there was expression  of 3 viruses, and in six (33,3%) patients — of two viruses, in 11 patients (61,1%) — one virus antigen. Total follow-up lasted for 19,3±3,7 months. Effectiveness of primary RFA in patients with intact myocardium was  88,9%,  with fibrous  changes  — 46,2%,  in myocarditis  — 34,4%.  Early recurrent  episodes of arrhythmia were absent  in unchanged myocardium (53,8%) and rarer  — late (34,6%). Having inflammatory changes led to reverse  relation, and later recurrent episodes developed more frequently (53,1%) and rarer — early (37,5%).Conclusion. By our data, only 24,5% patients do not have diseases that predispose to arrhythmias. Histologic study showed that only 10% patients have idiopathic type of arrhythmia, and a half have subclinic inflammatory changes of myocardium, the rest  have  fibrous  changes. Presence of  inflammatory  and  fibrous  changes in myocardium  increases the  quantity  of  early  and  late  arrhythmia  onsets   and, therefore,  double decreases RFA AF efficacy.